Self-Esteem Towards Consumptive Behavior in Eleventh Grade Female Students - Suryani, Yunita; Aipipidely, Diana; Mage, Mernon Yerlinda Carlista (Journal of Health and Behavioral Science, 2024)
Consumptive behaviour is the act of excessively purchasing goods for temporary pleasure, which can lead to feelings of anxiety and insecurity. Self-esteem is one of the factors that contribute to consumptive behaviour. Low self-esteem can lead individuals to experience feelings of depression and even psychosomatic disorders. The purpose of this study is to determine the effect of self-esteem on consumptive behaviour among 11th-grade female students at SMA N 3 Kota Kupang and to analyze the comparative level of the influence of self-esteem on consumptive behaviour between science (MIPA) and social studies (IPS) students. This research is quantitative and uses simple linear regression analysis techniques. The participants in this study were 86 female 11th-grade students. The data analysis results show that (H1) is accepted, meaning there is an effect of self-esteem on consumptive behaviour, and (H2) is rejected, meaning there is no comparative difference in the level of influence of self-esteem on consumptive behaviour between science and social studies students.